Assessing the Quality of Argumentative Texts: Examining the General Agreement Between Different Rating Procedures and Exploring Inferences of (Dis)agreement Cases - Landrieu, Yana; De Smedt, Fien; Van Keer, Hilde; De Wever, Bram (Frontiers in education (Lausanne), 2022)
Assessing argumentative writing skills is not a straightforward task, as multiple elements need to be considered. In function of providing feedback to students and keeping track of their progress, evaluating argumentative texts in a suitable, valid and efficient way is important. In this state-of-the-art exploratory study, 130 argumentative texts written by eleventh graders were assessed by means of three different rating procedures (i.e., absolute holistic rating, comparative holistic rating, and absolute analytic rating). The main aim of this study is twofold. First, we aim to examine the correlations between the three rating procedures and to study the extent to which these procedures differ in assigning scores. In doing so, the more innovative approach of pairwise comparisons is compared to more established assessment methods of absolute holistic and analytic rating. Second, we aim to identify key characteristics that determine the quality of an argumentative text, independent of the rating procedure used. Furthermore, key elements of mid-range, weak and strong argumentative texts were studied in detail. The results reveal low to moderate agreement between the different procedures, indicating that all procedures are suitable to assess the quality of an argumentative text; each procedure, however, has its own qualities and applicability.